PROGRESS IN DEVELOPMENT OF PUBLIC LOGISTIC CENTERS IN LITHUANIA AND SLOVAKIA - Buda, Martin; Babin, Matej; Klapita, Vladimir (Doprava a spoje, 2012)
The article points on the system solution of possibilities of development and construction of logistic centers in Slovakia and abroad on the basis of their purposeful comparative analysis. Public logistic centers have to fulfill the requirement of multimodality, or intermodality and have to create a functional network with enough transport potential.